2020
DOI: 10.3390/vaccines8020169
|View full text |Cite
|
Sign up to set email alerts
|

A Pentavalent Epstein-Barr Virus-Like Particle Vaccine Elicits High Titers of Neutralizing Antibodies against Epstein-Barr Virus Infection in Immunized Rabbits

Abstract: Primary infection with Epstein-Barr virus (EBV) is associated with acute infectious mononucleosis, whereas persistent infection is associated with chronic diseases such as autoimmune diseases and various types of cancer. Indeed, approximately 2% of all new cancer cases occurring annually worldwide are EBV-associated. Currently, there is no licensed EBV prophylactic vaccine. Selection of appropriate viral protein subunits is critical for development of an effective vaccine. Although the major EBV surface glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 76 publications
(117 reference statements)
0
20
0
Order By: Relevance
“…An effective vaccine could reduce the burden of a variety of diseases associated with EBV infection, including infectious mononucleosis and a wide range of B cell and epithelial cell cancers. A previous phase 2 trial with an EBV gp350 vaccine reduced rate of infectious mononucleosis, but failed to induce sterilizing immunity in clinic (10), suggesting that additional immunogens that target viral entry to epithelial cells may be required for a successful prophylactic vaccine (15,22). While EBV gp350 is important for attachment of the virus to B cells, it is not required for infection in vitro; in contrast, EBV gH, gL and gp42 are all essential for infection and EBV fusion to host cells.…”
Section: Discussionmentioning
confidence: 99%
“…An effective vaccine could reduce the burden of a variety of diseases associated with EBV infection, including infectious mononucleosis and a wide range of B cell and epithelial cell cancers. A previous phase 2 trial with an EBV gp350 vaccine reduced rate of infectious mononucleosis, but failed to induce sterilizing immunity in clinic (10), suggesting that additional immunogens that target viral entry to epithelial cells may be required for a successful prophylactic vaccine (15,22). While EBV gp350 is important for attachment of the virus to B cells, it is not required for infection in vitro; in contrast, EBV gH, gL and gp42 are all essential for infection and EBV fusion to host cells.…”
Section: Discussionmentioning
confidence: 99%
“…A humanized mouse model was also used to evaluate the protective efficacy of AMMO1 (63), and the results showed that the AMMO1 antibody could inhibit EBV infection. Some studies also used rabbits as animal models for EBV vaccine evaluation (22,27,28,51,56,155,156). The anti-EBV VCA titer and EBV DNA level could be detected in the blood of most rabbits after intravenous, intranasal, or peroral inoculation.…”
Section: Other Mammalian Modelsmentioning
confidence: 99%
“…However, the possibility of repacking of EBV DNA would bring safety concerns to such designs. In addition to the construction of VLPs based on EBV itself, a Newcastle disease virus-like particle (ND VLP) platform was also used for the presentation of EBV antigens such as gp350/gp220, combinations of gHgL-EBNA1 or gB/LMP2, and even pentavalent gp350/gH/gL/gp42/gB ( 47 , 56 ). It may be easier to produce VLPs by additional co-transfection of NDV-F for particle assembly, benefiting the rapid development of safe VLP vaccines.…”
Section: Vaccine Delivery Platforms and Formulationsmentioning
confidence: 99%
“… Optimization of prophylactic vaccine strategies. 1a, Cui et al, 2013 ; 1b, Kanekiyo et al, 2015 ; 1c, Zhao et al, 2018 ; 1d, Zhang et al, 2020 ; 1e, Kang et al, 2021 ; 2a,2b, Cui et al, 2016 ; 2c, Cui et al, 2021 ; 2d, Bu et al, 2019 ; 2e, Escalante et al, 2020 ; 3, Elliott et al, 2008 ; 4a,4b, Perez et al, 2017 ; 4c, van Zyl et al, 2018 . …”
Section: Optimization Of the Anti-ebv Vaccine Strategiesmentioning
confidence: 99%
“…This pentavalent (5-in-1) vaccine stimulated production of antibodies specific to the five glycoproteins capable of neutralizing EBV infection of the B cells as well as the epithelial cells. The IgG anti-gp350/220 and anti-gB levels were markedly higher than the IgG anti-gp42 and anti-gH/gL levels ( Escalante et al, 2020 ).…”
Section: Optimization Of the Anti-ebv Vaccine Strategiesmentioning
confidence: 99%